Endoderm-derived islet1-expressing cells differentiate into endothelial cells to function as the vascular HSPC niche in zebrafish - Nakajima, Hiroyuki; Ishikawa, Hiroyuki; Yamamoto, Takuya; Chiba, Ayano; Fukui, Hajime; Sako, Keisuke; Fukumoto, Moe; Mattonet, Kenny; Kwon, Hyouk-Bum; Hui, Subhra P.; Dobreva, Gergana; Kikuchi, Kazu; et al. (Developmental cell, 2023)
Endothelial cells (ECs) line blood vessels and serve as a niche for hematopoietic stem and progenitor cells (HSPCs). Recent data point to tissue-specific EC specialization as well as heterogeneity; however, it remains unclear how ECs acquire these properties. Here, by combining live-imaging-based lineage-tracing and single-cell transcriptomics in zebrafish embryos, we identify an unexpected origin for part of the vascular HSPC niche. We find that islet1 (isl1)-expressing cells are the progenitors of the venous ECs that constitute the majority of the HSPC niche. These isl1-expressing cells surprisingly originate from the endoderm and differentiate into ECs in a process dependent on Bmp-Smad signaling and subsequently requiring npas4l (cloche) function. Single-cell RNA sequencing analyses show that isl1-derived ECs express a set of genes that reflect their distinct origin. This study demonstrates that endothelial specialization in the HSPC niche is determined at least in part by the origin of the ECs.